Challenges and opportunities of peacebuilding in Colombia - Ovalle, Naomi; Pedrozo, Damaris (Ciencia y Academia, 2026)
This article explores the key elements for achieving lasting peace in Colombia, emphasizing the importance of addressing social inequalities and factors affecting vulnerable communities and victims of armed conflict. Through a literature review across databases, peacebuilding practices are identified, such as strengthening historical memory and implementing restorative justice. The article also considers approaches like “story listening,” which promotes healing and strengthens affected communities. Local initiatives, such as community sports, serve as tools to foster resilience and inclusion in areas with limited state presence. Finally, the analysis considers how the inclusion of ex-combatants and a balanced approach to justice (combining reconciliation with accountability) can help build a safer and fairer environment. Overall, these approaches suggest that a lasting peace depends on inclusive social reconstruction, which addresses both the emotional well-being of victims and the strengthening of community foundations in the post-conflict context.